السلطة الاستثنائية لمأمور الضبط القضائي في القبض على المتهم في الأحوال العادية وأحوال التلبس بالجريمة (Comprehensive Journal of Science, 2025)
The study dealt with the summer polices adveances in the meanings of the stowy on the accased… to please God, the seienhf, and exceptional case and an article about the rulers of God's law, the freedom of the criminal who improves the study clarified the conditions for the validity of the arrest carwied out by the judicial police officer, which were in cluded in the Libyan criminal procedure code exclusively, in addition to the conditions of people, an exceptional specialist, and arrestincases on the direct criminal action. As well asstating the effect resulting from the arrest procedure of guarantees police officer when arresting the accused and a ststment of the consequences of the arrest warrant issued by the udicial police officer..